Determination of antimicrobial resistance profiles and molecular detection of carbapenemases in Gram negative bacilli isolated from different sources in Mosul city, Iraq: DOI: 10.48129/kjs.17079 - Al-Hasso, Mahmood (Kuwait Journal of Science, 2022)
The objective of the present study was to evaluate the occurrence and dissemination of carbapenemases in Mosul city, Iraq. Bacterial isolates were recovered from clinical, veterinary, and environmental specimens and samples. Pure isolates were identified and tested for determination of their antimicrobial susceptibility profiles using disk diffusion method. Phenotypic detection of metallo-carbapenemase-producing bacteria was conducted using combined disk method. Imipenem-resistant strains were subjected to molecular detection of carbapenemase genes ( bla VIM , bla KPC , bla NDM , bla OXA-48 , bla IMP ) using multiplex PCR. Three hundred and ninety three bacterial isolates were recovered from (365) specimens and samples, 246 isolates (62.6%) were multi-drug resistant (MDR) and 49 isolates (12.5%) were resistant to imipenem. The study found that (7.4%) of the isolates were metallo-carbapenemase producers, phenotypically. Multiplex PCR results revealed that 47/49 (95.5%) imipenem-resistant isolates were positive for PCR detection test, isolates with double genes ( bla KPC + bla VIM and bla KPC + bla NDM ) were the most prevalent (n=9; 18.4% for each), followed by bla KPC and bla NDM (n=8; 16.3% for each), and bla VIM (n=6; 12.2% ). Three isolates (6.1%) were positive for bla IMP and two others (4.1%) were positive for each of bla OXA-48 and bla KPC + bla OXA-48 , while two isolates (4.1%) gave a negative result for the test. In conclusion, carbapenemase genes were detected in the environmental isolates as well as in the clinical and veterinary ones, which might suggest the transmission of carbapenemase-producing bacteria and /or resistance determinants from clinical and veterinary settings to the environment.